Probleme staatlicher Maßnahmen zur Entwicklung des ländlichen Raumes in Spanien.: Dargestellt am Plan Jaén und seinen agrargeographischen Folgen am oberen Guadalquivir - Tyrakowski, Konrad (ERDKUNDE, 1978)
The Plan Jaen of the year 1953 was intended to provide substantial improvement of the socio-economic conditions of the rural areas of the province of that name on the upper Guadalquivir river. The rural lower classes in particular were to benefit from these measures. The pressure of feudal conditions of production was to be relieved: state-organized job creation programmes were to reduce permanent unemployment; large estates in unfavourable situations hitherto cultivated only by rain-fed cultivation were to convert to irrigation and to be divided up; smallholders with 3-5 ha of land (full-time farming) and formerly almost landless day labourers with about 0.5 ha of land (subsidiary farming) were to be established in new settlement colonies. The practice of this subsidiary farming is the subject of special interest to this study. The colonists themselves differ greatly in their assessment of these subsidiary smallholdings. Since the number of jobs on the larges estates continues to decline and few are offered by rural industries, the small allotments by themselves fail to provide sufficient food. The result is massive emigration from the majority of these settlements. Thus the colonists' villages acquire the function of a selection process: once set on the path of mobility by trying out the offer of colonisation, the daily-paid labourers frequently follow their children into the cities. Others return to their home villages or try their luck in another colony. Those whom the state colonization programme did not intend to involve stay on: permanently employed labourers of the large estates and employees of the state. The land thus available is offered to them on unfavourable terms. It is hoped that purchases of additional land from the large landowners will enable small allotments to grow. But this will only help those colonists who remained behind. It is doubtful whether it will fill the vacant possessions in the villages and amortise the capital invested earlier.